Model Formasio Karakter Katekis Berbasis Pastoral Dasar - Tarihoran, Emmeria (Sekolah Tinggi Pastoral IPI Malang, 2025)
This study explores in depth the character formation model for catechists based on Basic Pastoral principles at Sekolah Tinggi Pastoral – IPI Malang using a qualitative case study approach. Data were collected through observations of daily spiritual practices, in-depth interviews with lecturers, mentors, and students, as well as document analysis of the curriculum and formation guidelines. The findings indicate that the formation process is not merely theoretical but is realized through the integration of the five pillars of Basic Pastoral—daily meditation, Scripture reading, liturgical prayer, self-formation, and community interview—into the academic, spiritual, and social life of the students. Mentors play a vital role as facilitators of faith and character growth, guiding students to internalize values such as honesty, humility, empathy, discipline, and readiness for mission. The model demonstrates significant positive impact on students’ reflective capacity, spiritual maturity, and pastoral identity. This research offers a meaningful contribution to the development of spirituality-based character education within Catholic higher education in Indonesia and provides insights applicable to broader contexts that aim to cultivate holistic and contextual catechist formation